Idiopathic infantile hypercalcemia with severe nephrocalcinosis, associated with mutations: a case report - Jeesun Yoo; Hee Gyung Kang; Yo Han Ahn (Korean Society of Pediatric Nephrology, 2022)
Nephrocalcinosis often occurs in infants and is caused by excessive calcium or vitamin D supplementation, neonatal primary hyperparathyroidism, and genetic disorders. Idiopathic infantile hypercalcemia (IIH), a rare cause of nephrocalcinosis, results from genetic defects in CYP24A1 or SLC34A1. Mutations in CYP24A1, which encodes 25-hydroxyvitamin D 24-hydroxylase, disrupt active vitamin D degradation. IIH clinically manifests as failure to thrive and hypercalcemia within the first year of life and usually remits spontaneously. Herein, we present a case of IIH wih CYP24A1 mutations. An 11-month-old girl visited our hospital with incidental hypercalcemia. She showed failure to thrive, and her oral intake had decreased over time since the age of 6 months. Her initial serum parathyroid hormone level was low, 25-OH vitamin D and 1,25(OH)2 vitamin D levels were normal, and renal ultrasonography showed bilateral nephrocalcinosis. Whole-exome sequencing revealed compound heterozygous variants in CYP24A1 (NM_000782.4:c.376C>T [p.Pro126Ser] and c.1310C>A [p.Pro437His]). Although her hypercalcemia and poor oral intake spontaneously resolved in approximately 8 months, we suggested that her nephrocalcinosis and renal function be regularly checked in consideration of potential asymptomatic renal damage. Hypercalcemia caused by IIH should be suspected in infants with severe nephrocalcinosis, especially when presenting with failure to thrive.